The Development of the Awareness in Electricity Power Consumption of Residents in Bang Kruai Community, Nonthaburi Province - Hansonthia, Arak; Supanyo, Weerachat; Ratana-Ubol, Archanya (Journal of Education Studies, Chulalongkorn University, 2020)
This research is an action research study with the aim to develop a non-formal education process that merges the ideas in order to build awareness of the residents in the Bang Kruai community regarding electrical power usage. The conduction of the research can be divided into 5 steps, which consisted of 1) the preparation step, 2) the planning step, 3) the execution step, 4) the results observation step, and 5) the reflective step. The sample group consisted of 15 people from the residential population of the Bang Kruai district who have willingly participated in the process. Research tools included recorded observations and conversation topics for each step of the research. Data was analyzed with a written description of the research’s commencement and the drafting of a conclusion regarding the non-formal education process. Research results discovered that the non-formal education process that merges ideas in order to build awareness of the residents regarding electrical power usage consist of 4 steps as follows: Step 1 Preparing to face problems, which clarifies the objectives of activities and the necessity of conserving electrical power for participants; Step 2 Determining conditions for self-checks, which allow for participants to realize the causes of wasteful electrical power usage and to create action plans to reduce electrical power together; Step 3 Giving freedom in their learning and allowing each person to test their action plans on their own, and Step 4 The reflection of learned and changed behaviors in order to reflect the value of the action plans and to assess their changed behavior regarding electrical power usage.